2006
DOI: 10.1111/j.1439-0396.2005.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of benzoic acid on growth performance, nutrient digestibility, nitrogen balance, gastrointestinal microflora and parameters of microbial metabolism in piglets

Abstract: In order to investigate the effects of benzoic acid on growth performance, nutrient digestibility, nitrogen balance and gastrointestinal microflora of piglets, we conducted a performance experiment and a separate balance study. The performance experiment involved four different dietary treatments: (1) basal diet (negative control); (2) basal diet supplemented with benzoic acid at 5 g/kg; (3) basal diet supplemented with benzoic acid at 10 g/kg; (4) basal diet supplemented with potassium diformate at 12 g/kg. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
107
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 23 publications
12
107
2
3
Order By: Relevance
“…Previous studies have confirmed that inclusion of 0.5-1.0% BA could improve growth performance (Kluge et al 2006;Torrallardona et al 2007) and protein digestibility (Guggenbuhl et al 2007) in weanling pigs.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous studies have confirmed that inclusion of 0.5-1.0% BA could improve growth performance (Kluge et al 2006;Torrallardona et al 2007) and protein digestibility (Guggenbuhl et al 2007) in weanling pigs.…”
Section: Introductionmentioning
confidence: 81%
“…Therefore, no control groups were included to evaluate the beneficial effects of BA, EO and E. faecium. Previous studies have established the positive effects of BA on growth performance and nutrient digestibility (Kluge et al 2006;Torrallardona et al 2007) in weaned piglets. In agreement with their results, we found that 0.5% BA plus EO increased ADG and G/F from d 8 to 21 and during the overall period.…”
Section: Discussionmentioning
confidence: 99%
“…This study also suggests that the inclusion of 5000 ppm benzoic acid in weaners' feed had beneficial effects on growth performance compared to control group, as shown by the decrease of diarrhoea score, (though there was not a significant influence on total piglets' morbidity), the decrease of faecal E. coli counts and the increase of BW and ADG, without any influence on FCR. Previous studies (Maribo et al 2000, Kluge et al 2006, Øverland et al 2007 indicated that benzoic acid causes a marked reduction of the density and activity of gastro-intestinal bacteria as well as a strong bactericidal effect on both coliform and lactic acid bacteria in the swine stomach content and in the digesta from the small intestine. The reduction of diarrhoea in BA group in the present study could be attributed to the reduction of the presence and activity of E. coli and the establishment of a proper balance between beneficial and pathogenic microorganisms in the intestine.…”
Section: Discussionmentioning
confidence: 97%
“…The use of benzoic acid in pig feed resulted in multiple beneficial effects on growth performance of pigs (Maribo et al 2000, Kluge et al 2006, Torrallardona et al 2007, Bü hler et al 2009) and displayed an important antibacterial activity in gastrointestinal microbial control, especially against coliforms (Knarreborg et al 2002, Kluge et al 2006, Piva and Grilli 2007, Øverland et al 2007). Such antimicrobial activity may be of interest to reduce diarrhoea incidence of piglets after weaning (Gheler et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A promising alternative to antibiotics are organic acids, which include short-chain fatty acids (SCFA), which are ''generally regarded as safe'' compounds with one or more carboxyl groups and less than six carbons in their molecular formula. These have been used for many decades in the terrestrial animal feed industry as an antimicrobial and growth promoter (Thompson and Hinton 1997;Kluge et al 2006). In more recent years, organic acids such as lactic, formic, citric and propionic acids and their associated salts have been the focus of research for use in aquatic animal feeds Koh 2011, 2016;Sukor et al 2016).…”
Section: Introductionmentioning
confidence: 99%